2020
DOI: 10.1590/2177-6709.25.1.064-069.oar
|View full text |Cite
|
Sign up to set email alerts
|

Impact of catastrophizing on pain during orthodontic treatment

Abstract: Objective: This study proposed to investigate the influence of catastrophizing and others factors related to pain during orthodontic treatment. Methods: 27 patients with 0.022 x 0.028-in Straight-wire brackets were evaluated during alignment and leveling phase with nickel-titanium wires. Visual Analog Scales measured the intensity of orthodontic pain at six moments after a clinical appointment: 6 first hours; 1, 2, 3, 5, and 7 days. Multiple linear regression and stepwise approach assessed the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Despite that, there are controversial results about the correlation between the irregularity index and the perception of pain. Some studies found that there is no correlation [52][53][54], but a recent one found that crowding is a risk factor, and with each increase in crowding, there is a 1.10 times increase in painful sensation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, there are controversial results about the correlation between the irregularity index and the perception of pain. Some studies found that there is no correlation [52][53][54], but a recent one found that crowding is a risk factor, and with each increase in crowding, there is a 1.10 times increase in painful sensation [55].…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the pain scores between the 5th and 7th day after activation decreased to baseline values, which is also in agreement with some previous studies. 2,4,5,18 The activation at the first appointment (T1) induced significantly higher and longer pain than T2 and T3 (Figure 1). These findings corroborate with previous studies and may be explained by initial soft tissues injuries caused by orthodontic appliances.…”
Section: Discussionmentioning
confidence: 99%
“…No significant association was found at T2 and T3. Some studies suggested that catastrophising influences pain after placement of orthodontic separators 5,10 and during brackets debonding 11 ; however, another study evaluated cross-sectional catastrophising during orthodontic treatment and showed no strong influence on pain perception. 5 It was suggested that the initial activation caused less pain than the brackets debonding or the use of separators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations